Global Health Security (GHS) index model extension and assessment of the Western Balkan countries position - Marija Panić; Živan Živković (University American College Skopje, 2021)
The paper discusses the assessment of global health security based on the extension of the Global Health Security (GHS) index basic model (prevention, de- tection and reporting, rapid response, health system, compliance with international standards, and environmental risk) with parameters: Gross Domestic Product (GDP) per capita, Democracy Index (DI) and Corruption Perceptions Index (CPI), using mul- tiple linear regression analysis (MLRA) and artificial neural networks (ANNs). Based on the size of the coefficient of determination (R2), the validity of the extension of the basic GHS model was evaluated based on the results achieved on a sample of 42 coun- tries. In the second part of the study, the results of individual segments of the inter- national safety assessment of health systems for the countries of the Western Balkan (WB) countries are discussed, by comparing them with countries of similar size in the EU. The results showed that health security systems in WB countries are at a much lower level compared to countries of similar size in the EU, which was also reflected in the COVID 19 pandemic during 2020 and 2021. In WB countries, in the post-pandemic period, the consequences in different areas (human health, economy, culture, edu- cation, etc.) will be much more visible in relation to EU countries with a significantly higher degree of development of health systems defined by the GHS model.
Keywords: 330; GHS model; GHS model extension; EU; Western Balkan countries